METAKOGNITIF, PROSES SAINS, DAN KEMAMPUAN KOGNITIF MAHASISWA DIVERGEN DAN KONVERGEN DALAM PBL - Yusran Khery; Subandi Subandi; Suhadi Ibnu (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2013)
The purpose of this study was: (1) determine differences in metacognitive awareness and cognitive abilities of students who learned with PBL and conventional strategies, (2) determine differences in metacognitive awareness, science process skills, and cognitive abilities among students with divergent thinking and character convergent strategies are learned with PBL. This study uses three different kinds of design that is descriptive research design, quasi-experimental design, and pre-experimental design to answer the research objectives numbered one through three in a row. The instrument used in this study were: (1) questionnaire divergent thinking and convergent character, (2) metacognitive awareness questionnaire, (3) observation sheets science process skills, and (4) tests of cognitive ability. Data were analyzed by inferential statistics. The results showed that: (1) there is no difference in metacognitive awareness and cognitive skills of students with learning strategies derived from PBL and conventional strategies, (2) there are no differences in metacognitive awareness and cognitive abilities among students divergent and convergent. Science process skills students better than the divergent-convergent.